Effect of Modified Roux-en-Y Gastric Bypass Surgery on GLP-1, GIP in Patients with Type 2 Diabetes Mellitus - Shao-Wei Xiong; Jing Cao; Xian-Ming Liu; Xing-Ming Deng; Zeng Liu; Fang-Ting Zhang (Gastroenterology Research and Practice)
The type 2 diabetes mellitus (T2DM) is one of the most serious diseases that threaten public health. Modified gastric bypass surgery has been applied to the treatment of T2DM patients in the 1990s, but the therapeutic mechanism to this function is still unclear. The aim of this study was to further clarify the effect and the mechanism of modified gastric bypass surgery on glucose metabolism in patients with T2DM. In the study, the incretin indexes and blood glucose indexes were analyzed before surgery and 1 week and 1, 3, and 6 months after surgery. The results suggested that modified Roux-en-Y gastric bypass can promote GLP-1 secretion in patients with T2DM, while reducing the secretion of GIP. Thus it could effectively control blood glucose of patients with T2DM.